Autoridades locales conflictuadas: temores y dificultades de jueces territoriales en Chile colonial (1711-1817) - María Eugenia Albornoz Vásquez (Nuevo mundo - Mundos Nuevos, 2015)
The analysis of reports sent to their superiors and messages sent to other people and written during the judicial proceedings for slanders enables a reflexion upon the obstacles encounterd by men in charge of the functions of urban and rural judges in the XVIIIth century in Chile. Different levels of competences and skills appear as difficulties, according to the ability or clumsiness of these men. Their fears reveal a sensibility and the reluctance to suffer in their duty, and their acts of rebellion underscore the individual resistance to the rules of their office. This article aims at showing the experience and the trajectories of individuals who practiced as judges and undermining their subjectivity, as well as the singularity of an office frequently studied from the perspective of legality or institutional corporatism. It allows to question the judicial, juridical and jurisdictionnal practices and culture in the last decades of the colonial period.